Inhibitors of α-amylase and α-glucosidase from Andromachia igniaria Humb. & Bonpl. (December 2015) - Saltos, Mariela Beatriz Vera; Puente, Blanca Fabiola Naranjo; Faraone, Immacolata; Milella, Luigi; Tommasi, Nunziatina De; Braca, Alessandra
Graphical abstract: Highlights: A phytochemical study of Andromachia igniaria was carried out. Sixteen compounds including two new flavonoids were isolated and characterized. The hypoglycemic properties of extracts and pure compounds were evaluated. Abstract: Two new flavonoids, (2 S )-3', 4', 7, 8-tetrahydroxyflavanone 7- O -(6"- O -acetyl)-β-d -glucopyranoside (1 ) and 3', 4', 7, 8-tetrahydroxyflavone 7- O -(6"- O -acetyl)-β-d -glucopyranoside (2 ) along with fourteen known compounds were isolated from Andromachia igniaria aerial part extracts. Their structures were determined via spectroscopic analyses including 2D NMR. The hypoglycemic properties of all extracts and pure compounds were evaluated measuring α-amylase and α-glucosidase inhibitory effects. The n -butanol among the extracts was found to be the best inhibitor of both α-amylase and α-glucosidase enzymes, while among compounds the most active were: bidenoside F and luteolin 4'- O -β-d -glucopyranoside as α-amylase inhibitors; eriodictyol, butein and okanin as α-glucosidase inhibitors. Results demonstrated that A. igniaria can represent an important natural source with high biological values, helpful to control postprandial hypoglycemia.